A Literature Survey on Offline Automatic Algorithm Configuration - Eryoldaş, Yasemin; Durmuşoglu, Alptekin (Applied sciences, 2022)
Metaheuristic and heuristic methods have many tunable parameters, and choosing their values can increase their ability to deal with hard optimization problems. Automated approaches for finding good parameter settings have attracted significant research and development efforts in the last few years. Because parameter tuning became commonly utilized in industry and research and there is a significant advancement in this area, a comprehensive review is an important requirement. Although there is very wide literature about algorithm configuration problems, a detailed survey analysis has not been conducted yet to the best of our knowledge. In this paper, we will briefly explain the automatic algorithm configuration problem and then survey the automated methods developed to handle this problem. After explaining the logic of these methods, we also argued about their main advantages and disadvantages to help researchers or practitioners select the best possible method for their specific problem. Moreover, some recommendations and possible future directions for this topic are provided as a conclusion.